Modulação microglial na doença de Alzheimer - Barbosa, Marina Zanichelli [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
There are many questions to be solved about Alzheimer's Disease (AD), although studies are advancing significantly. There are many unenlightened mechanisms about pathogenesis and no form of prevention or cure. It is known that in the development of the disease the microglia can undergo alteration of phenotype and that this can directly influence the neuron. In order to understand more about the neuroimmune interactions existing in Alzheimer's disease, this project has as main objective to investigate when and how the M2 microglia pattern changes to M1 in the triple transgenic model (3xTg-AD), the murine model that most closely resembles the disease in humans. This pattern change reflects on neurodegeneration and is related to beta-amyloid plaques and neurofibrillary tangles. We know that increased production of reactive oxygen species (ROS) accompanies the change from M2 to M1 phenotype, which is responsible for the release of proinflammatory cytokines that may be directly toxic to neurons. Therefore, we want to know at what moment and what mechanism is involved in the change of the microglia activation pathway from the alternative phenotype (M2) to the classic (M1) in 3xTg-AD mice, the AD triple transgenic model.

Ainda há muitas lacunas para serem preenchidas sobre a Doença de Alzheimer (DA), embora os estudos estejam avançando de forma significativa. Existem muitos mecanismos não esclarecidos sobre a patogênese e nenhuma forma de prevenção ou cura. Sabe-se que no desenvolvimento da doença a microglia pode sofrer alteração de fenótipo e que isso pode influenciar diretamente o neurônio. A fim de entender mais sobre as interações neuroimunes existentes na Doença de Alzheimer, esse projeto apresenta como principal objetivo investigar em que momento e de que forma ocorre a alteração do padrão de microglia M2 para M1 no modelo triplo transgênico (3xTg-AD), o modelo murino que mais se assemelha a doença em humanos. Essa alteração de padrão reflete na neurodegeneração e está relacionada às placas beta-amiloides e emaranhados neurofibrilares. Sabemos que o aumento da produção de espécies reativas de oxigênio (EROs) acompanha a alteração do fenótipo M2 para M1, o qual é responsável pela liberação de citocinas pró-inflamatórias que podem ser diretamente tóxicas para os neurônios. Sendo assim, queremos saber em que momento ocorre e qual mecanismo está envolvido na mudança da via de ativação da microglia do fenótipo alternativo (M2) para o clássico (M1) em camundongos 3xTg-AD, triplo transgênico para DA.
Keywords: Alzheimer, Doença de; Cerebro - Doenças; Microglia; Camundongo como animal de laboratorio; Brain - Diseases